Changes in aging-induced kidney dysfunction in mice based on a metabolomics analysis - Jiao, Danli; Qi, Li; Hu, Li; Hu, Dan; Li, Xiao; Li, Guona; Li, Zheying; Liu, Shimin; Zhao, Chen; Wu, Huangan (Frontiers in Endocrinology, 2022)
Kidney dysfunction is particularly important in systemic organ injuries caused by aging. Metabolomics are utilized in this study to explore the mechanism of kidney dysfunction during aging by the identification of metabolites and the characterization of metabolic pathways. We analyzed the serum biochemistry and kidney histopathology of male Kunming mice aged 3 months and 24 months and found that the aged mice had inflammatory lesions, aggravated fibrosis, and functional impairment. A high-resolution untargeted metabolomics analysis revealed that the endogenous metabolites in the kidneys and urine of the mice were significantly changed by 25 and 20 metabolites, respectively. A pathway analysis of these differential metabolites revealed six key signaling pathways, namely, D-glutamine and D-glutamate metabolism, purine metabolism, the citrate cycle [tricarboxylic acid (TCA) cycle], histidine metabolism, pyruvate metabolism, and glyoxylate and dicarboxylate metabolism. These pathways are involved in amino acid metabolism, carbohydrate metabolism, and nucleotide metabolism, and these can lead to immune regulation, inflammatory responses, oxidative stress damage, cellular dysfunction, and bioenergy disorders, and they are closely associated with aging and kidney insufficiency. We also screened nine types of sensitive metabolites in the urine as potential biomarkers of kidney dysfunction during the aging process to confirm their therapeutic targets in senior-induced kidney dysfunction and to improve the level of risk assessment for senile kidney injury.